Artificial intelligence and project management : an integrated approach to knowledge-based evaluation - Grzeszczyk, Tadeusz A. (Abingdon, Oxon ; New York, NY : Routledge, 2024)
"Although some people had considerable doubts about the usefulness of such solutions in the past, AI plays a growing role in modern business. It can be expected that the interest in it will also lead to an increase in supporting the planning, evaluation and implementation of projects. In particular, the proper functioning of multifaceted evaluation methods has a crucial impact on the appropriate planning and execution of various types of projects, as well as the effective achievement of the organization's goals. This book offers a presentation of complex problems and challenges related to the development of AI in project management, proposing an integrated approach to knowledge-based evaluation and indicating the possibilities of improving professional practical knowledge in this field. The unique contribution of this book is to draw attention to the possibilities resulting from conducting transdisciplinary research and drawing on the rich achievements in the field of research development on knowledge-based systems that can be used to holistically support the processes of planning, evaluation and project management. The concept of the integrated approach to knowledge-based evaluation is presented, developed as a result of drawing inspiration from the systems approach, praxeology and selected AI mathematical models. Presented in a highly accessible manner, the book discusses mathematical tools in a simple way, which enables understanding of the content by readers across broad subject areas who may be not only participants of specialist training and university students but also practitioners, consultants, or evaluators. Supported by pedagogical features, this book will be a valuable resource for academics and upper-level students in particular across project management related fields and of great interest to all those looking to understand the challenges and effectiveness of AI in business"--
Keywords: Project management; Artificial intelligence; BUSINESS & ECONOMICS / General; BUSINESS & ECONOMICS / Business Ethics; BUSINESS & ECONOMICS / Decision-Making & Problem Solving